2020
DOI: 10.1155/2020/8914367
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Intraoperative Fluid Administration and Outcomes of Pancreatoduodenectomy

Abstract: Background. Intraoperative fluid (IOF) administration plays an important role during major abdominal surgery although increased fluid intake can adversely influence postoperative outcomes. However, the effect of the IOF rate on the outcomes of pancreatoduodenectomy (PD) is unclear. Methods. 151 patients, who underwent PD at Binzhou Medical University Hospital between January 2010 and May 2017, were categorized into three groups according to IOF rates (ml/kg/hr): restricted (<10, n=47), standard (10–15, n=76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The relationship between intraoperative fluid balance and the specific abdominal complication of POPF is also ambiguous. Some studies have demonstrated that the incidence of POPF in the high fluid volume group was higher than that in the low fluid volume group during PD, and intraoperative fluid excess was also considered a risk factor for POPF [19][20][21][22][23]. Nevertheless, in 2017, a meta-analysis evaluated the relationship between the perioperative fluid balance and postoperative complications of PD (including POPF), and no significant correlation was found [24].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intraoperative fluid balance and the specific abdominal complication of POPF is also ambiguous. Some studies have demonstrated that the incidence of POPF in the high fluid volume group was higher than that in the low fluid volume group during PD, and intraoperative fluid excess was also considered a risk factor for POPF [19][20][21][22][23]. Nevertheless, in 2017, a meta-analysis evaluated the relationship between the perioperative fluid balance and postoperative complications of PD (including POPF), and no significant correlation was found [24].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intraoperative uid balance and the speci c abdominal complication of POPF is also ambiguous. Some studies have demonstrated that the incidence of POPF in the high uid volume group was higher than that in the low uid volume group during PD, and intraoperative uid excess was also considered a risk factor for POPF (19)(20)(21)(22)(23). Nevertheless, in 2017, a meta-analysis evaluated the relationship between the perioperative uid balance and postoperative complications of PD (including POPF), and no signi cant correlation was found (24).…”
Section: Discussionmentioning
confidence: 99%
“…The de nition of POPF is relatively uniform in many studies, but the calculation of perioperative uid balance or uid management varies. There is no uniform standard for the de nition of perioperative uid balance or uid management, especially for the cutoff values, which can vary (20)(21)(22)(23), and this makes it di cult to integrate and summarize the results of current clinical studies. Relevant research results should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Gilgien et al [ 46 ] also concluded that patients who received ≥4400 ml intravenous fluids during the first 24 h after surgery had more complications, especially pulmonary complications. Liberal fluid therapy may also lead to an increase in postoperative pancreatic fistula (POFF) formation [ 47 ]. Some authors argue that both ultra-restrictive and ultra-liberal fluid therapy are not optimal [ 48 ].…”
Section: Discussionmentioning
confidence: 99%